Droga na szczyt i droga w otchłań – kilka uwag o karierze Flawiusza Stilichona - Wilczyński, Marek (Vox Patrum, 2018)
The most important factors responsible for development of an impressive career of Flavius Stilicho were: his family ties with Theodosians’ dynasty, the way he reorganized the Roman army, military victories, how he drummed up senate’s support for his political aims and the balanced policy of using and stopping the barbarian tribes. Protecting emperor Honorius, cooperating simultaneously with pagan and Christian fractions in the senate, achieving military success and defending borders of the Roman Empire against barbarians raids, Stilicho de facto was reigning the state in the name of his son-in-law, Honorius. Paradoxically, the same factors contributed to the downfall of the master-in-chief in 404-408 A.D. The conflict with his wife, Serena, and his son-in-law, Honorius, the mutiny in the army called-up by the reforms of Stilicho, some disagreements with the senate caused by the case of Melania the Younger and compensation for Alaric and, at last, the invasion of barbarian tribes on Gaul in 406 A.D. destroyed the carefully built career of Flavius Stilicho. He didn’t decide to keep his high rank by triggering off a civil war, what differed him clearly from his followers, Flavius Aetius and Flavius Ricimer.